A comparison of code blue calls in a tertiary pediatric hospital in the pre-pandemic and pandemic periods - Sevda Akdeniz; Hatice Selcuk Kusderci; Senay Canikli Adiguzel (Medicine Science, 2023)
This study compares the code blue calls (CBCs) used in our hospital before and during the COVID-19 pandemic. CBCs made between 31.03.2018 and 31.03.2022 in the Samsun Maternity and Child Health Training and Research Hospital were examined retrospectively. The study period was subdivided into two sections, one from March 31, 2018, to March 30, 2020 (Group 1, the pre-pandemic period) and the other from March 31, 2020, to March 31, 2022 (Group 2, the pandemic period). Patients' demographic data, the reason for the CBC and where it was issued, the time elapsed before the team arrived on the scene, and the outcomes were then compared between the groups. Seventy-nine CBCs, 34 (43.1%) of which were ‘false,' were included in the study. Forty-six calls were made in the pre-pandemic period, 26 (56.5%) of which were true calls, while 33 calls were made during the pandemic, of which 19 (57.6%) were true calls. Twenty-seven (60%) of the 45 true CBCs were for boys and 18 (40%) for girls. The children's mean age was 73.06±66.85 months, and 57.7% of the CBCs were issued during the pre-pandemic period. No significant difference was observed between groups 1 and 2 in terms of code blue team arrival times (114.03±59.14 vs. 138.1±95.96 sec, respectively (P=.305). The total mortality rate at the end of 30 days was 13.3% (P=.679). No difference was observed in CBC results between the pre-pandemic and pandemic periods in this study. We think that some blue code parameters, such as false calls and blue code team arrival times, can be improved through effective training against potential future pandemics. [Med-Science 2023; 12(4.000): 1206-9]